OsDWD1 E3 ligase‐mediated OsNPR1 degradation suppresses basal defense in rice. (21st October 2022) - Choi, Changhyun; Im, Jong Hee; Lee, Jinjeong; Kwon, Soon Il; Kim, Woe‐Yeon; Park, Sang Ryeol; Hwang, Duk‐Ju
SUMMARY: Many ubiquitin E3 ligases function in plant immunity. Here, we show that Oryza sativa (rice) DDB1 binding WD (OsDWD1) suppresses immune responses by targeting O. sativa non‐expresser of pathogenesis‐related gene 1 (OsNPR1) for degradation. Knock‐down and overexpression experiments in rice plants showed that OsDWD1 is a negative regulator of the immune response and that OsNPR1 is a substrate of OsDWD1 and a substrate receptor of OsCRL4. After constructing the loss‐of‐function mutant OsDWD1R239A, we showed that the downregulation of OsNPR1 seen in rice lines overexpressing wild‐type (WT) OsDWD1 (OsDWD1WT ‐ox) was compromised in OsDWD1R239A ‐ox lines, and that OsNPR1 upregulation enhanced resistance to pathogen infection, confirming that OsCRL4 OsDWD1 regulates OsNPR1 protein levels. The enhanced disease resistance seen in OsDWD1 knock‐down (OsDWD1‐kd) lines contrasted with the reduced disease resistance in double knock‐down (OsDWD1/OsNPR1‐kd) lines, indicating that the enhanced disease resistance of OsDWD1‐kd resulted from the accumulation of OsNPR1. Moreover, an in vivo heterologous protein degradation assay in Arabidopsis thaliana ddb1 mutants confirmed that the CUL4‐based E3 ligase system can also influence OsNPR1 protein levels in Arabidopsis . Although OsNPR1 was degraded by the OsCRL4 OsDWD1 ‐mediated ubiquitination system, the phosphodegron‐motif‐mutated NPR1 was partially degraded in the DWD1‐ox protoplasts. This suggests that there might be another degradation process for OsNPR1. Taken together, these results indicate that OsDWD1 regulates OsNPR1 protein levels in rice to suppress the untimely activation of immune responses. Significance Statement: NPR1 (non‐expresser of pathogenesis‐related gene 1), master regulator in plant immunity and systemic acquired resistance, was regulated by a ubiquitin‐proteasome system (UPS) that has been well studied in the model plant Arabidopsis. In this study, we discovered that Oryza sativa CRL4‐DDB binding WD1 (OsDWD1) was a substrate receptor of the CRL4 complex and that OsNPR1 could be targeted and degraded by the OsDWD1‐mediated ubiquitination system.